PERCEPÇÃO DOS RIBEIRINHOS DO IGARAPÉ SANTA CRUZ SOBRE A CAPTAÇÃO DE ÁGUA DO IGARAPÉ PARA UTILIZAÇÃO DOMÉSTICA - BARRETO, Cristiane Alves (2024)
Disorganized urban growth began in the second half of the 20th century, Brazil became an urban country, that is, more than 50% of its population came to live in cities. Since the 1950s, the process of urbanization in Brazil has become more and more accelerated if it is spreading throughout the national territory. In this phase of reoccupation of the countryside to the city, it triggered serious problems such as the change in the original scenario and brought to light the environmental problem. It is in this context that the urban expansion process that Breves-PA, over the years has been incorporating in its spaces, and the occupations in unoccupied areas mark and spaces of the city, being greater population agglomeration, mainly in the peripheral zones the banks of the Santa igarapé Cruz, entailing scenarios of environmental problems of various orders. In view of these scenarios, the objective of this work was to identify the real situation of the Igarapé Santa Cruz, as well as a brief study regarding the perception of the riverside inhabitants regarding the abstraction of water for use in various domestic activities.